Workshop on Kurikulum Merdeka (Freedom Curriculum): Dismantling Theories and Practices - Taufik Mulyadin; Muhammad Khoiron; Dion Ginanto; Kristian Adi Putra (BEMAS: Jurnal Bermasyarakat, 2023)
The enactment of Ministerial Decree of the Minister of Education, Culture, Research and Technology, the Republic of Indonesia Number 56/ M/ 2022 on the Guidance of Curriculum Implementation for Learning Recovery in early 2022 has marked the implementation of a new curriculum, namely ‘Kurikulum Merdeka’ or Freedom Curriculum in Indonesian educational system. The new curriculum brings certain novelties as compared to the previous (Curriculum 2013), for instance focusing on essential contents, providing freedom to students, teachers, and school in the implementation, and employing relevant and interactive activities in learning through project works. To successfully implement Kurikulum Merdeka, the curriculum users, particularly teachers, have to gain solid understanding about the curriculum. Hence, working with Dunia Akademisi, Bina Nusantara (Binus) University organized a workshop on Kurikulum Merdeka targeting teachers and teacher students throughout Indonesia. The workshop focused on discussing theories from which the curriculum had been developed and ways to use it in the classroom. The event was carried out online by using Zoom and YouTube and attended by 300 and over 2.000 participants in each respective platform. By their participation in the workshop, they were expected to have better understanding and readiness to implement the curriculum in their schools as well as classrooms. In overall, the participants were satisfied with the overall organization of the event and the speakers, found the event fulfilling their expectation, and gained useful lesson from the event. Certain recommendations were yielded, which are increasing Zoom capacity, carrying out better preparation, and making the event into a series instead.